Pentecostalism in Contemporary Posters Communication Using Graphic Design Poster Templates As Example - Onyemachi, Nwabueze Umezurike; Uzzi, Festus O. (NIU Journal of Social Sciences; Vol 7 No 2 (2021): KIU Journal of Social Sciences, Vol. 7 No. 2, June 2021, 2021)
Posters, posters and posters everywhere! Many of the posters seem in open spaces around us are visual announcement of the Christian religion. This is largely due to the proliferation of Pentecostalism, which explicitly necessitates production of posters - visual messages that advertises churches and their activities.  This paper is an attempt to guide direction in the brand of Christian religion posters and design presentation.  It interrogates the technical knowledge (know-how) of graphic poster designers and the churches as stakeholders; and attests to an uncontrolled indigenous designs approach that is neither here nor there. In the context of formal circle of representation and laws of formal organization, this paper posits for what is proper and acceptable within practice of designing posters for visual communication. Keywords: Poster Advert, Graphic Designers, Poster Clients, Visual communication, Technical Know-how